Information Technology Training Increases Student Digital Insights Through Diffusion Of Innovations Theory: Pelatihan Teknologi Informasi Meningkatkan Wawasan Digital Siswa Melalui Teori Difusi Inovasi - M. Rizal Habibi; Ilmi Usrotin Choiriyah; Nabila Salma; Dewi Fatimah; Silvia Islami (Proceedings of The ICECRS, 2025)
General Background Information technology constitutes an integral component of modern life, requiring robust digital insights as a crucial competency for young generations. Specific Background Although structured information technology training programs aim to equip students with essential skills, widespread digital divides and resource limitations continue to constrain educational institutions in Indonesia. Knowledge Gap While ideal frameworks suggest that information technology training yields high digital proficiencies, empirical realities indicate that numerous students lack adequate competencies due to variable training quality and equipment shortages. Aims This qualitative case study analyzes the outcomes of Microsoft Word and Canva training among grade ten students at SMA Negeri 1 Krian. Results Findings demonstrate that the training substantially increases students' capabilities in generating automated tables of contents and designing simple posters, supported by the diffusion of innovation framework, while generating positive self-confidence despite equipment limitations. Novelty This research specifically applies the diffusion of innovation theory to evaluate relative advantage, compatibility, complexity, trialability, and observability within a secondary school digital training context. Implications Educational stakeholders must develop sustainable information technology training programs integrated directly into core school curricula. Highlights: structured sessions successfully elevate student competencies in creating automated document tables of contents and graphic design posters participants exhibit increased self-confidence and creative application of digital tools despite institutional equipment constraints establishing sustainable instructional programs integrated into standard school curricula remains essential for long-term digital progress Keywords: Information Technology Training, Digital Insight, Diffusion Of Innovations, Software Competency, Student Creativity